Operationalizing positive-constructive pedagogy to artificial intelligence: the 3E model for scaffolding AI technology adoption - Jaakkola, Maarit (Frontiers in Communication, 2025)
This reflective essay outlines a positive-constructive pedagogy as an approach to enhancing AI literacies of different types, with a focus on the individual’s personal relationship to AI technologies. It is argued that personal relationships with emerging technologies are crucial for a successful implementation of AI in society, as understanding of AI needs a personal contact with the technology and tacit knowledge about it to develop. AI thus poses a societal learning challenge, which can be met by lending space for personal attitudes, affects, and reflections of media users from the outset, supporting them gradually toward a critical and deepened relationship to the tools and software they are using.